1989
DOI: 10.1063/1.344087
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion-induced deformations of polymeric substrates: Particle size dependence of the contact area

Abstract: Adhesion-induced deformations of a polyurethane substrate in contact with cross-linked polystyrene spheres, having diameters ranging from less than 2 μm to approximately 12.5 μm were observed using scanning electron microscopy. The diameters of the contact areas were measured from the micrographs. It was found that the contact radius varied as the particle radius raised to the 0.75±0.05 power. Experimental results are compared to the predictions of various adhesion models. The results are also discussed in ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 19 publications
0
41
0
Order By: Relevance
“…2.1a. However, many experiments have found that small particles could have a large contact radius in adhesive contact with elastic substrates, even under a zero external loading [14,15] as shown schematically in Fig. 2.1b.…”
Section: Theoretical Modelmentioning
confidence: 98%
“…2.1a. However, many experiments have found that small particles could have a large contact radius in adhesive contact with elastic substrates, even under a zero external loading [14,15] as shown schematically in Fig. 2.1b.…”
Section: Theoretical Modelmentioning
confidence: 98%
“…Samples for contact area studies were prepared by a procedure described by Rimai et al (20,21). Samples for determining the roughness of the PSL were prepared two different ways, depending upon whether we were studying roughness of unused or used (in AFM removal force studies) PSL colloids.…”
Section: Preparation Of Samplesmentioning
confidence: 99%
“…To determine the maximum allowable contact area a procedure developed by Rimai was followed (16,21). This involved allowing PSL spheres to settle on a silicon substrate and then gold-coating the substrate.…”
Section: Contact Area Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, current theories do not always predict the correct power law dependence of the contact radius on particle radius. For example, it has been found that the contact radius of micrometer size particles in contact with elastomeric substrates can vary as the particle radius to the 3/4 power [28][29][30] rather than the 2/3 power, as predicted by the JKR theory. This paper reports results obtained from a first principles approach to the problem of particle adhesion.…”
Section: Introductionmentioning
confidence: 95%